Señorita Extraviada - Portillo, Lourdes (United States : Lourdes Portillo, 2001)
A haunting investigation into a mysterious crime wave amid the disorders and corruption of one of the biggest border towns in the world. Between 200 and 400 girls have been murdered in Juárez, Mexico, where authorities ignore pleas for justice from the victims' families, crimes go unpunished, evidence of government complicity remains uninvestigated, and the killings continue to this day.
Soros Documentary Fund
Soros Documentary Fund
Keywords: Documentary films